2010
DOI: 10.1021/np900829g
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolyzable Tannins of Tamaricaceous Plants. III. Hellinoyl- and Macrocyclic-Type Ellagitannins from Tamarix nilotica

Abstract: Three new hellinoyl-type ellagitannins, nilotinins M4 (7), D7 (8), and D8 (9), and a new macrocyclic-type, nilotinin D9 (10), together with eight known tannins, hirtellins B (2), C (11), and F (12), isohirtellin C (13), tamarixinin A (3), tellimagrandins I and II, and 1,2,6-tri-O-galloyl-beta-d-glucose (14), were isolated from an aqueous acetone extract of Tamarix nilotica dried leaves. Nilotinin M4 (7) is a monomeric tannin possessing a hellinoyl moiety. The structure of 8 demonstrated replacement of one of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 28 publications
3
46
0
Order By: Relevance
“…The review of literature reported the isolation of monomeric (Isohirtellin C, Remurin A-B, Gemin D, Nilotinin, Nilotinin M2-7, Hippomanin A, and Tellimagrandin I-II), dimeric (Nilotinins D1-D10, Tamarixinin A-C and Hirtellin A-D and F), trimeric (Nilotinin T1-T2, Hirtellin T1-T3) and tetrameric ellagitannins (Nilotinin Q1) from the aqueous acetone extracts of leaves of T. nilotica growing in Egypt [10,[34][35][36][37]. Interest in the ellagitannin constituents due to their marked antiviral, antimicrobial, immunomodulatory, antitumor, and hepatic protective activities, which are largely dependent on the tannin structures [38] (Figure 3).…”
Section: Ellagitanninsmentioning
confidence: 99%
See 1 more Smart Citation
“…The review of literature reported the isolation of monomeric (Isohirtellin C, Remurin A-B, Gemin D, Nilotinin, Nilotinin M2-7, Hippomanin A, and Tellimagrandin I-II), dimeric (Nilotinins D1-D10, Tamarixinin A-C and Hirtellin A-D and F), trimeric (Nilotinin T1-T2, Hirtellin T1-T3) and tetrameric ellagitannins (Nilotinin Q1) from the aqueous acetone extracts of leaves of T. nilotica growing in Egypt [10,[34][35][36][37]. Interest in the ellagitannin constituents due to their marked antiviral, antimicrobial, immunomodulatory, antitumor, and hepatic protective activities, which are largely dependent on the tannin structures [38] (Figure 3).…”
Section: Ellagitanninsmentioning
confidence: 99%
“…Ellagitannins from the leaves of T. nilotica grown in Egypt were reported to exhibit significant host-mediated antitumor activities against sarcoma-180 in mice and strong cytotoxic effects with higher tumor specificity against four tumor cell lines [35,37]. T. nilotica showed a selective cytotoxic potential against liver (HUH-7), colon (HCT-116), lung and breast (MCF-7) carcinoma cell, while being non-toxic to other cancer cells [9,40].…”
Section: Cytotoxic and Anti-angiogenic Activitymentioning
confidence: 99%
“…As in the condensed tannin cases, pure hydrolyzable tannin spectra reflect the chemistry of each [32][33][34][35]. Again the fingerprint of each tannin manifests itself clearly in the spectrum of each respective tanned leather.…”
Section: Tanning With Hydrolyzable Tanninsmentioning
confidence: 99%
“…Roots revealed the presence of gallic acid derivatives, a lignan (syringaresinol) and isoferulic acid, niloticol, and 3-hydroxy-4-methoxycinnamaldehyde (Barakat et al, 1987). Leaves revealed the presence of nilotinins M1, M4, D2, D3, D7, D8, D9, hirtellins B, C, F, tamarixinin A, 1,2,6-tri-O-galloyl-D-glucose, methyl ferulate 3-O-sulphate, coniferyl alcohol 4-O-sulphate, kaempferol 4'-methyl ether, tamarixetin and quercetin 3-O-beta-D-glucupyranuronide (Orabi et al, 2009(Orabi et al, , 2010Abouzid et al, 2009). Moreover, flowers revealed isolation of the methyl and ethyl esters of gallic acid, pmethoxygallic acid, kaempferol, quercetin 3-Oglucuronides, the 3-O-sulphated kaempferol 7,4'-dimethyl ether and the free flavonols, besides the digalloylglucose and niloticin (Nawwar et al, 1982(Nawwar et al, , 1984aNawwar and Souleman, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidant and hepatoprotective activities were evaluated for total flower extract (Abouzid et al, 2008;Abouzid and Sleem, 2011), moreover, nilotinin D8 and hirtellin A isolated from leaf extract were found active against the human oral tumor cell lines, human squamous cell carcinoma (HSC-2, HSC-3, and HSC-4) and human promyelocytic leukemia (HL-60) cells (Orabi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%